The effects of the Covid-19 pandemic on ecotourism, a study from West of Iran - Rahimian, Mehdi; Masoudi Rad, Mandana; Zareei, Hossein (Frontiers in Public Health, 2022)
Most tourism researchers agree on the effects of the COVID-19 on ecotourism. The present study aims to assess the effects of the COVID-19 pandemic on the ecotourism status in Lorestan province in Iran. To this aim, 29 effects were identified using Delphi technique. According to results, the effects were divided into six categories including the decreased number of incoming tourists, the reduced activity of hotels and resorts, the declined income of goods and service suppliers for tourists, the decreased activity of travel agencies and tourist tours, as well as positive and negative environmental effects. Generally, the results provide new knowledge in the field of ecotourism crisis management. In addition, the identified effects provide the basis for further research on the method of reducing the negative effects.